Index of equality of floors: overcoming of a gender gap (Вестник КазНУ. Серия Экономическая, 2016)
In system of public administration there is a tendency when often men take the highest official places at the level of adoption politically of deci-sions, in turn women take places in the lowest control link.In this regard in the present article the index of equality of floors, meth-odology of calculation of an index of equality of floors is considered, the treatment is given to the concept «gender gap», the main results of research of a gender inequality in four spheres are considered, the list of the entered countries of a regional hub in a rating on the level of a gender inequality is considered, data of the Republic of Kazakhstan are analysed, the assess-ment is given to the state gender policy, recommendations about improve-ment of gender aspects in public service are made. Also in article need of carrying out policy of settlement of gender relationship in public service as which purpose proportional division of men and women has to serve the literacy level, and also complexity of the decided tasks in system of public administration according to their professionalism, reveals.
Keywords: государственное управление; страны регионального хаба; индекс равноправия полов; гендерный разрыв; гендерный аспект мемлекеттік басқару; аймақтық хаб елдері; жыныс тардың тең құқылығы индексі; гендерлік алшақтық; гендерлік аспект